2019
DOI: 10.7287/peerj.preprints.27557v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fish nursery value of algae habitats in temperate coastal reefs

Abstract: The nursery function of coastal habitats is one of the most frequently mentioned and recognized ecosystem services in the valuation of coastal ecosystems. Despite its importance our understanding of the precise habitat parameters and mechanisms that make a habitat important as a nursery area is still limited for many species. The study aimed to establish the importance of different algae morphotypes in providing shelter and food for juvenile coastal fish during the main settlement peaks in early spring and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Habitat and seascape tri-dimensional structure can be qualified by its heterogeneity and complexity 83,84 . Generally high quality habitats for juvenile fishes are recognized to be associated with high degrees of three-dimensional structuration 85 , in terms of both complexity 46,48,86,87 and/or heterogeneity 36 . Natural rocky habitats (RS) presented a high structural and biological complexity due to different macrophytes assemblages, and indeed supported the highest mean species richness and abundance of juvenile fishes whatever the period.…”
Section: Habitats Used By Juvenile Fish In Mediterranean Shallow Coasmentioning
confidence: 99%
See 2 more Smart Citations
“…Habitat and seascape tri-dimensional structure can be qualified by its heterogeneity and complexity 83,84 . Generally high quality habitats for juvenile fishes are recognized to be associated with high degrees of three-dimensional structuration 85 , in terms of both complexity 46,48,86,87 and/or heterogeneity 36 . Natural rocky habitats (RS) presented a high structural and biological complexity due to different macrophytes assemblages, and indeed supported the highest mean species richness and abundance of juvenile fishes whatever the period.…”
Section: Habitats Used By Juvenile Fish In Mediterranean Shallow Coasmentioning
confidence: 99%
“…However, the higher abundance of juveniles in seagrass bed habitats and rocky substrates during the warm period could be related to the greater protection and food resources provided by the greater canopy height of Posidonia oceanica and macroalgae communities 45,46,48 . The role of highly complex Cystoseira forest canopies with regard to the composition of juvenile fish assemblage was well studied by Cheminée et al 45,46 , Cuadros et al 47 and Hinz et al 48 , who demonstrated that Symphodus spp., Labrus spp. and Serranus spp.…”
Section: Importance Of Both Local Habitat Characteristics and Large-smentioning
confidence: 99%
See 1 more Smart Citation
“…Macroalgal forests and seagrass meadows provide numerous ecosystem services and have been proved to be key nursery habitats, essential for the life cycle maintenance of many coastal fishes in the Mediterranean Sea [3] [13]. Several studies suggest a positive relationship between macrophyte three-dimensional structural complexity and its key role in fish recruitment, by providing increased potential prey and shelter from predators [4] [10] [14] [18].…”
Section: Introductionmentioning
confidence: 99%
“…Canopy-forming macroalgae are also colonized by a diverse and abundant fauna of mobile benthic invertebrates (Wikstrom & Kautsky 2007, normally dominated by amphipods, isopods, gastropods and polychaetes (Tano et al 2016), and constitute both reproduction sites and nursery habitats for many other larger species (Hinz et al 2019), where juveniles find effective shelter from predators and adequate foraging grounds (Edgar et al 2004). As such, canopy-forming algae constitute a semi-closed biodiversity loop, containing a self-sustained food-web, which include the main algal host and their epiphytic algal assemblages as a basal trophic level, direct mesoherbivore grazers and detritivores as intermediate levels and small fish and invertebrate predators as high within-canopy trophic levels.…”
Section: General Introductionmentioning
confidence: 99%